Vitamin K: A novel cancer chemosensitizer. (18th January 2022) - Gul, Sameena; Maqbool, Muhammad Faisal; Maryam, Amara; Khan, Muhammad; Shakir, Hafiz Abdullah; Irfan, Muhammad; Ara, Chaman; Li, Yongming; Ma, Tonghui
Abstract: Cancer incidences are growing rapidly and causing millions of deaths globally. Cancer treatment is one of the most exigent challenges. Drug resistance is a natural phenomenon and is considered one of the major obstacles in the successful treatment of cancer by chemotherapy. Combination therapy by the amalgamation of various anticancer drugs has suggested modulating tumor response by targeting various signaling pathways in a synergistic or additive manner. Vitamin K is an essential nutrient and has recently been investigated as a potential anticancer agent. The combination of vitamin K analogs, such as vitamins K1, K2, K3, and K5, with other chemotherapeutic drugs have demonstrated a safe, cost‐effective, and most efficient way to overcome drug resistance and improved the outcomes of prevailing chemotherapy. Published reports have shown that vitamin K in combination therapy improved the efficacy of clinical drugs by promoting apoptosis and cell cycle arrest and overcoming drug resistance by inhibiting P‐glycoprotein. In this review, we discuss the mechanism, cellular targets, and possible ways to develop vitamin K subtypes into effective cancer chemosensitizers. Finally, this review will provide a scientific basis for exploiting vitamin K as a potential agent to improve the efficacy of chemotherapeutic drugs. Abstract :